Spiritual Development in Design and Technology Subjects as a Fortress Against Students' Negative Innovative Thinking - Zaipah binti Ismail; Aede Hatib Bin Musta’amal @ Jamal; Nornazira binti Suhairom; Rohana binti Hamzah (PT. Intelek Cendikiawan Nusantara, 2024)
The Standard Secondary School Curriculum (KSSM) Design and Technology (RBT) is to produce students with positive innovative thinking. These skills will enable students to create unique, useful, and harmless products. However, the current era of digitalization pushes students towards negative innovative thinking. Negative innovative activities carried out by a few students are increasing and worrying all parties. Therefore, spiritual development should be applied in RBT subjects as a fortress against the negative innovative thinking of students. This study aims to discuss the importance of spiritual growth in Design and Technology subjects so that it can be a fortress against the negative innovative thinking of students. The bibliography method is used in this qualitative study to better understand the subject being studied. This study refers to material from scholarly sources such as books, articles, and proceedings papers. The results of the research show that spiritual development is very important to produce students who have faith in God, responsibility as a servant, and caliph as a fortress against negative innovative thinking. This study shows that spiritual development in Design and Technology subjects is very important to be a fortress for students from negative innovative thinking. Next, this study can guide educators to produce more quality and meaningful education.